Vulnerable Narcissism and Internet Addiction: Exploring Mediating Pathway through Vengeance - Ozkan Cikrikci; Ragip Umit Yalcin (Journal of Education in Science, Environment and Health)
The present study aimed to explore the mediating pathway on internet addiction through vengeance. The sample was consisted of 392 university students (N female = 242, 61.7% and N male = 150, 38.3%). The ages ranged between 18 and 35, with a mean age of 21.6 (SD = 1.95). The sample completed Young's Internet Addiction Test-Short Form, The Vengeance Scale, and Hypersensitive Narcissism Scale. According to mediation analysis results using structural equation modeling and bootstrapping, vengeance partially mediated vulnerable narcissism-internet addiction association. The results of the present study intimated the importance of the effects of individual differences and communication styles or preferences on internet addiction. The possible potential therapeutic power of vulnerable narcissism, which may lead to a direct increase in vengeance and an indirect increase in internet addiction through vengeance, appeared in line with this perspective. Finally, the results provided beneficial outcomes for clinical experts.